Field notes contributed by Joseph P. Schaufenbuel, December 2, 1981 - Schaufenbuel, Joseph P.et al (1981)
Field notes were contributed by Joseph P. Schaufenbuel and John C. Robinson, observer. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1981. Epson - sheet feed